Electrochemistry and STM-assisted Molecular electronics study of bimetallic hexaphyrins - Quintans, Ciro Scheremeta (Universidade Federal de São Carlos, 2019)
ELECTROCHEMISTRY AND STM-ASSISTED MOLECULAR ELECTRONICS STUDY OF BIMETALLIC HEXAPHYRINS. The electron transport in porphyrinoids are related to several bioprocesses in Nature, from conversion from solar energy to chemical energy in photosynthesis to the transport and reduction of oxygen in aerobic animals. Due to these characteristics, several bioinspired applications have used this class of materials, photovoltaics, water splitting, catalysis and photodynamic therapy. To further understand how this process occurs in expanded porphyrins, 5 hexaphyrins in Hückel aromaticity were synthesized, with and without metal centres. These molecules were characterized by spectroscopy, electrochemistry and through molecular break junctions. The absorption spectrum of hexaphyrins show several possibly transitions, which splits and broadens with the addition of metal centres due to the degeneration of the molecule’s orbitals. The spectroscopic band gap was characterized by fluorimetry showing a gap between 1.12 to 1.20 eV for the molecules synthesized. Electrochemistry measurements shows several distinct quasi-reversible redox pairs. The addition of metal centres shifted the processes accordingly to the electronegativity of the metal centres. Due to the severe number of reactions a diagnosis criterium was developed to indicate which peaks corresponds to reactions in the macrocycle or its ligands and which are likely to occur on the metal centres. The molecular conductance of the hexaphyrins were studied with STM assisted break junctions on non-modified and modified gold as electrodes. The gold modification was proved necessary due to the lack of interactions between the molecules and the metal electrodes. Several current signatures were observed on 4-TPy modified gold. This corresponds to all possible molecular junction conformations. Upon the addition of metal centres, a similar trend is observed for each metal, indicating that the molecule properties do not impact as much as the conformation of the molecular wire.
Electrochemistry and STM-assisted Molecular electronics study of bimetallic hexaphyrins
Keywords: Eletroquimica; Electrochemistry; Molecular Electronics; Eletronica Molecular; Porfirinas; Porphyrins; STM; CIENCIAS EXATAS E DA TERRA::QUIMICA